Application of Acacia Honey Dressing to Post-Debridement Wound Care in Type 2 Diabetes Patients - Dewa Darma, Dimas; Rosidah, Istiqomah; Nurazizah, Wika (Jurnal Riset Media Keperawatan, 2025)
Type 2 diabetes mellitus (DM) is a chronic disease whose prevalence continues to increase in Indonesia. One complication of DM is difficult-to-heal wounds due to chronic hyperglycemia, impaired tissue perfusion, decreased angiogenesis, and peripheral neuropathy. If the wound experiences necrosis or infection, debridement is often performed to support the healing process. Purpose to describe the application of honey therapy to the wound care process in patients with type 2 DM post-debridement. Methodology This study used a descriptive method with a treatment period of 12 months. Honey therapy was administered for three days, with a frequency of one treatment per day. Results showed improvement in wound condition. On the third day, Mr. Y showed improved skin integrity: Upgraded to level 4, reduced redness, moisturized skin, reduced peeling, and a feeling of comfort. Mr. T also showed similar improvements with improved skin texture, increased moisture, and reduced redness.